A Method of Analyzing the Porous Microstructure in Air-Entrained Concrete on the Basis on 2D Image Analysis. (2015) - Wawrzeńczyk, Jerzy; Kozak, Wioletta
Abstract: The number of air voids, their size and disposition in cement paste, are important characteristics, which substantially affect the system of air voids that protects concrete from freezing and thawing cycles. The standard spacing factor L is based on the simplified Powers model, which assumes that all bubbles have the same diameter and are distributed in cube corners. A better solution is provided by Philleo, which determines the percentage content of protected paste ( S* ). The authors' approach consists in determining the PPV factor, which is based on the concept of Philleo, and takes into account not onlythe actual structure of air voids, butalso of aggregate grains, which is often disregarded in analyses. In this article the results of analyzing the air void structure in air-entrained concrete on the basis on 2D image analysis are presented. Implementation of this research was possible thanks to the use of a special procedure of concrete samples preparation.Such an approach allows the separation of 4 phases of concrete: aggregate, cement paste, rings of the paste protected by air voids and air. The PPV results obtained from image analysis were compared with standard spacing factor L and with Philleo factor ( S* ).The authors are of the opinion that the 2D analysis proposed in the study will make it possible to describe more accurately the air-void system in air-entrained concrete.